Diagnosis and diagnostic tests for fibromyalgia (syndrome) - F. Wolfe; W. Häuser (PAGEPress Publications, 2012)
Objectives: To present diagnostic criteria for the clinical diagnosis of fibromyalgia syndrome (FMS) and to offer a scheme for diagnostic work-up in clinical practice. Methods: Narrative review of the literature, consensus documents by the American College of Rheumatology (ACR), evidence-based interdisciplinary German guidelines on the diagnosis and management of FMS. Results: The ACR 1990 classification criteria emphasized tender points and widespread pain as the key features of FMS. In 2010, the ACR proposed preliminary diagnostic criteria for fibromyalgia that abandoned the tender point count and placed increased emphasis of patient symptoms. A later modification of the ACR 2010 criteria for use in surveys employed a self-report questionnaire (Fibromyalgia Survey Questionnaire FSQ) to assess patient symptoms. The FSQ can be used to assist physician's diagnosis of FMS. We recommend a stepwise diagnostic work-up of patients with chronic widespread pain (CWP) in primary care: Complete medical history including medication, complete medical examination, basic laboratory tests to screen for inflammatory or endocrinology diseases, referral to specialists only in case of suspected somatic diseases, assessment of limitations of daily functioning, screening for other functional somatic symptoms and mental disorders, and referring to mental health specialists in case of mental disorder. Conclusions: The diagnosis of FMS is easy in most patients with CWP and does not ordinarily require a rheumatologist. A rheumatologist's expertise might be needed to exclude difficult to diagnose or concomitant inflammatory rheumatic diseases. In the presence of mental illness referral to a mental health specialist for evaluation is recommended.